Towards enabling construction organizations’ adaptation to environmental sustainable construction in developing countries - Mensah, Sarfo; Ayarkwa, Joshua; Nani, Gabriel (Advances in Social Sciences Research Journal, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">Giant strides have been taken in developed countries towards the achievement of sustainable development goals. This has been pursued largely through the establishment of relevant policies and regulations and that significantly require the construction industry’s role. Environmental sustainability is foundational as far as the pursuit of sustainable development is concerned. However, in developing countries, construction organizations are yet to be enabled to adapt to Environmental Sustainable Construction. How can these organizations be enabled to adapt to ESC? The aim of this paper is to find out enablers of construction organizations’ adaptation to ESC in developing countries. A review of literature on the enablers of sustainability within the construction industry has be conducted and the need to identify enablers within the context of developing countries have been revealed. A content analysis of qualitative data obtained from an averagely 1½ hour in-depth interview of 13 construction organizations has been used to develop a relational model outlining primary elements required to enable commencement of regularization of ESC practices. On this basis, a conceptual framework explaining different time zones required for regularizing ESC, has been developed. Thus, a clear direction towards the development of a broader framework towards construction organizations’ adaptation to ESC in a developing country context has been provided.